The grey seal, Halichoerus grypus (Fabricius), in Finnmark, Norway - Wiig, Øystein ([Fiskeridirektoratets havforskningsinstitutt], 1987)
The distribution, abundance and breeding season of grey seals in Finnmark, Norway are reviewed. The seals are divided into eight hypothetical stocks: Sørøya, Magerøya, Laksfjord, Tanafjord, Kongsfjord, Syltefjord, Vardø and Varangerfjord. Breeding has been verified for five of these stocks. The total minimum observed stock size is 353 grey seals, but the real number is probably much higher. The breeding season seems to be in October-November west of Nordkapp and in December in the eastern part of the county.